GENETIC AND INFECTIOUS FACTORS PREDISPOSING TO PERIODONTITIS ON THE BACKGROUND OF OSTEOPENIA - Hurtova, Y.M.; Dienha, O.V.; Litovkin, K.V.; Vyshnevska, H.O.; Shnaider, S.A.; Hayduchok, I.H.; Dorosh, I.V. (World of Medicine and Biology, 2023)
The purpose of this study was to examine the association of single nucleotide polymorphisms of TNFSF11, TNFRSF11B, SOST, ZNF385B and LRP5 genes involved in bone metabolism with the risk of periodontitis, as well as to assess the infection of the oral cavity with Porphyromonas gingivalis in the presence of periodontitis, osteopenia and periodontitis with osteopenia. The study included patients with periodontitis (13 patients), osteopenia (8 patients), periodontitis with osteopenia (11 patients) and a control group (23 patients). The A-allele of the rs6757845 G>A polymorphism of the ZNF385B gene increased the risk of periodontitis in the heterozygous state and in the dominant inheritance model. Differences between the study groups in the distribution of frequencies of genotypes and alleles of other polymorphisms were not statistically significant. The number of Porphyromonas gingivalis bacteria in gingival sulcus/periodontal pocket fluid samples of patients with osteopenia and periodontitis with osteopenia was significantly higher than in the control group and the group of patients with periodontitis.
Keywords: osteopenia; oral health; polymorphism; genotyping; oral bacteria